2010
DOI: 10.1074/jbc.m110.145946
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a New Multigene Family Encoding Isomaltases in the Yeast Saccharomyces cerevisiae, the IMA Family

Abstract: It has been known for a long time that the yeast Saccharomyces cerevisiae can assimilate ␣-methylglucopyranoside and isomaltose. We here report the identification of 5 genes (YGR287c, YIL172c, YJL216c, YJL221c and YOL157c), which, similar to the SUCx, MALx, or HXTx multigene families, are located in the subtelomeric regions of different chromosomes. They share high nucleotide sequence identities between themselves (66 -100%) and with the MALx2 genes (63-74%). Comparison of their amino acid sequences underlined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 66 publications
(39 reference statements)
8
75
0
Order By: Relevance
“…This confirmation does not exclude the possibility that the data of Pougach et al. (2014) are correct, since they used a different S. cerevisiae strain (KV5000, which originates from BY4741, an S288c-derived strain) whilst Teste, François and Parrou (2010) used the CEN.PK113-7D strain.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmation does not exclude the possibility that the data of Pougach et al. (2014) are correct, since they used a different S. cerevisiae strain (KV5000, which originates from BY4741, an S288c-derived strain) whilst Teste, François and Parrou (2010) used the CEN.PK113-7D strain.…”
Section: Discussionmentioning
confidence: 99%
“…The MALS genes encode α-glucosidases that allow yeast to metabolize complex carbohydrates like maltose, isomaltose, and other α-glucosides [32],[33]. Several key features make this family ideal to study duplicate gene evolution.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that for expression of the IMA genes, the presence of the AGT1 gene responsible for isomaltose and α methylglucoside transport into the cell was required [39]. Growth on isomaltose may depend on the maltose activator gene MAL23p [38]. The expression of IMA1 and IMA5 genes is induced by maltose, isomaltose, and α methylglucoside.…”
Section: Expression Of the Ima Genesmentioning
confidence: 98%
“…The function of the IMA genes was studied thor oughly by Teste et al [38]. The cloning and expression of the IMA genes on the yeast plasmid made it possible to determine the activity of the corresponding enzymes on different substrates: p nitrophenyl α D glucopyranoside, maltose, maltotriose, α methylglu coside, and isomaltose.…”
Section: Expression Of the Ima Genesmentioning
confidence: 99%
See 1 more Smart Citation